2005
DOI: 10.1167/iovs.04-0542
|View full text |Cite
|
Sign up to set email alerts
|

Internalization ofPseudomonas aeruginosaIs Mediated by Lipid Rafts in Contact Lens–Wearing Rabbit and Cultured Human Corneal Epithelial Cells

Abstract: These findings demonstrate that contact-lens-mediated PA internalization involves lipid raft formation. Also, hTCEpi cells may be used as an experimental model for studying further the molecular mechanism(s) of PA infection in the corneal epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
53
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 39 publications
3
53
1
Order By: Relevance
“…This finding was not anticipated, in view of previous reports that had suggested that P. aeruginosa is internalized at advanced stages of pulmonary infection, possibly via a receptor located in the basolateral membrane (16). While this putative receptor remains to be identified, a possible role for CFTR has been suggested (22,26,43), even though this chloride channel is normally located within the apical membranes of epithelial cells (32,55). In this situation, access to the basolateral membrane is not needed for P. aeruginosa to interact with CFTR, in contrast to the finding of such an early access documented in this and previous studies (19).…”
Section: Discussionmentioning
confidence: 81%
“…This finding was not anticipated, in view of previous reports that had suggested that P. aeruginosa is internalized at advanced stages of pulmonary infection, possibly via a receptor located in the basolateral membrane (16). While this putative receptor remains to be identified, a possible role for CFTR has been suggested (22,26,43), even though this chloride channel is normally located within the apical membranes of epithelial cells (32,55). In this situation, access to the basolateral membrane is not needed for P. aeruginosa to interact with CFTR, in contrast to the finding of such an early access documented in this and previous studies (19).…”
Section: Discussionmentioning
confidence: 81%
“…The images in panel C show representative cells from three separate experiments that were performed. Bars ϭ 10 m. (21,49). Internalization of LFA-1 could occur either independent of or in association with lipid rafts (14).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that invasion requires bacterial interaction with host cell targets such as lipid rafts (39,66,67), which are themselves associated with specific targets for P. aeruginosa invasion, for example, the cystic fibrosis transmembrane conductance regulator (38,49) and asialo-GM1 (10). These targets interact with bacterial invasion ligands, including lipopolysaccharide (LPS), flagellin, and pili (10,22,69).…”
mentioning
confidence: 99%